Association of Quality of Life and Pain Intensity in Patients of Trigger Points : Quality of Life and Pain Intensity - Ali Kazim, Syed; Nawaz, Arshemah; Taha Javed, Muhammad; Liaquat, Mariam; Noor, Sara; Sheeraz, Muhammad; Hashim, Adnan (Pakistan Journal of Health Sciences, 2023)
Myofascial trigger points are hyperirritable, unpleasant when compressed, and they have the ability to generate anomalies of the autonomic nervous system, referred pain, and motor dysfunction. Objective: To determine the Association of quality of life and pain intensity in patients of trigger points. Methods: Data were gathered from the Central Park Teaching Hospital, the Mayo Hospital, the Doctors Hospital, and the Jinnah Hospital. Our investigation focused on the prevalence of disability and quality of life in patients with trigger points. For quality of life and pain, we used the SF 36 Functional Limitation and General Health questionnaire; a visual analog scale was used. Results: Out of 152 patients, 87(57.2%) were males, and 65(42.8%) were females. The patients mean age was 38 ± 12.78 yrs. with a minimum age of 22 yrs. And maximum age of 72 yrs. 4(2.6%) patients has mild Pain, 67(44.1%) have moderate pain, 81(53.3%) have severe pain. 67(44.1%) patients have poor Health quality, 81(53.3%) have moderate health quality, and 4(2.6%) have good health quality. P-value for pain intensity and general health was 0.00, so we reject the null hypothesis and accept the alternative hypothesis, which indicated a significant difference between pain intensity and general health. p-Value was 0.012 for pain intensity and physical functioning. Conclusion: Hence it was concluded that the majority of the patients with trigger points have a poor quality of life and severe Pain. There was an association between quality of life and pain intensity.